Facile one-step preparation and characterization of graphene quantum dots suspension via electrochemical exfoliation - Danial, Wan Hazman; Farouzy, Bashariah; Abdullah, Mundzir; Abdul Majid, Zaiton (2021)
The study reports on the production graphene quantum dots (GQDs) suspension using simple electrochemical setup which involved electrolyte solution, consisting of citric acid and sodium hydroxide (NaOH) mixture, and pristine graphite rods were used for the electrode without any heating treatment (calcination), thusly avoid any high energy consumption. The balanced reaction mixture of citric acid and NaOH was used to investigate the effects of reaction time and voltage used towards the production of GQDs. UV-Vis spectroscopy analysis revealed significant UV absorption around 240-255 nm which depicted π→π* transition of aromatic sp2 C-C bonds while FTIR analysis showed the significant C=C stretching band around 1635 cm-1 attributed by the aromatic ring. The exfoliation of the GQDs increased as the concentration of NaOH in electrolyte, time taken and voltage increased. The optimum GQDs suspension can be produced using the balanced ratio of citric acid and NaOH with a voltage of 10 V for 2 hours reaction time. TEM analysis confirmed the presence of the GQDs obtained with average size of ~5nm for the optimum GQDs suspension. The exfoliation of GQDs via the electrochemical technique might pave the way towards upscale and sustainable production of the nanomaterial.